Improving distance courses: Understanding teacher trainees and their learning styles for the design of teacher training courses and materials at a distance - Dzakiria, Hisham (Anadolu University, 2004)
Literature on distance education and teacher education seems to show that what we do not know about Distance Teacher Trainees1 ( DTT ) and their learning process involved exceeds what we know about it.As more DTT enroll in distance education programmes globally, distance education providers and institutions will witness trainees coming with different backgrounds and experiences begin to take advantage of this learning opportunities.One important variable in the effectiveness of distance learning is the preference of the distance learner for a particular learning mode.A key to maintaining distance learners participation in learning lies in understanding the Learning Styles Preferences ( LSP ) and the processes involved.This is also true for teacher training.There is much greater variation in the range of LSP and how to address them when preparing distance training materials and courses. The primary purpose of this paper is to propose ways in which individual learning differences should be accommodated when designing instructional learning materials in print for DTTs.Kolb’s ( 1984 )model on learning cycle and styles are discussed to provide instructional design guidelines which accommodate each stage of the learning cycles and individual differences between DTT in processing and presenting information and knowledge.In addition, issues on teacher education, distance learning, individual differences, and ways in which the ‘differences’ can be accommodated when designing learning materials for DTT are also discussed. This paper resonates the idea and belief that if attempts are made to match learning styles of DTTs and andragogy with content to be learned, distance teacher educators ( DTEs )and instructors can develop better instructional materials with greater prospects of success. Getting to know and understand the teacher trainees and their learning process involved must first be addressed to facilitate the diverse needs of the Malaysian teacher trainees.